Overdose effect of aconite containing Ayurvedic Medicine (‘Mahashankha Vati’) - Panda, Ashok Kumar (Medknow Publications, 2010)
There are chances that the use of larger than recommended dose of Ayurvedic medicines containing aconite can produce drug reactions. Vatsanabha (Aconitum ferox Wall.) is a very well-known ingredient of Ayurvedic formulations and is prescribed as an antipyretic, analgesic, anti-rheumatic, appetizer and digestive. The recommended dose of purified Vatsanabha (A. ferox Wall.) root is 15 mg. We present a case of hypotension and bradycardia due to aconite poisoning caused by overdosing of an Ayurvedic medicine (Mahashankha Vati), which was primarily managed by Ayurvedic treatment.